KNOWLEDGE AND ACTIONS OF LEPROSY PATIENTS ON THE INCIDENCE OF LEPROSY IN BRENGKOK VILLAGE, BRONDONG PUBLIC HEALTH CARE OF LAMONGAN REGENCY, INDONESIA - Khunafa', Alifatun; Prasetyo, Aries; Wiyono, Trimawan Heru; Asyary, Al (Public Health of Indonesia, 2019)
Background: Leprosy is an infectious disease that can cause physical disability, as well as social, economic, and cultural problems. The prevalence of leprosy in Indonesia is still high.Objective: The purpose of this study was to determine patients' behavioral factors that influence the incidence of leprosy.Methods: An ex-post-facto analysis with a case-control approach was used. The population of the study was the entire Brengkok Village community. The sampling technique is a fixed-disease sampling method, in which the all cases (34 persons) are clinically proven leprosy sufferers and the controls (34 persons) are the comparable neighbors of the sufferers. Data analysis was done using a chi-square test, and the risk of disease was measured by the odd ratio (OR).Results: Testing for differences between the case and the control group resulted in p = 0.000 for knowledge about the cause of leprosy, p = 0.005 for detecting an early sign of leprosy, p = 0.000 for knowledge about the transmission of leprosy, and p = 0.000 for affecting the incidence of leprosy. The results showed that there was a relationship between the level of knowledge and the incidence of leprosy (p = 0.002), while the OR value obtained is 7.50 (CI: 2,168 - 25,946). Furthermore, testing for differences between the case and the control group yielded  p = 1.000 for the use of different clothes; p = 0.000 for the use of different bathing tools; p = 0.000 for the use of different towels, which means there is a connection between the use of towels and the incidence of leprosy; and p = 0.003 for the use of different footwear. In addition, there is a relationship between the actions of people and the incidence of leprosy (p = 0.000), while the OR value obtained was 59,933 (CI: 13.131 - 273,557).Conclusion: The knowledge and actions of people affected by leprosy are predisposing factors associated with the incidence of leprosy and are risk factors for the disease. Knowledge about the transmission of leprosy and the activity of using different towels are the most important factors influencing the incidence of leprosy.